2019
DOI: 10.3390/drones3030056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rotor–Airframe Orientation on the Aerodynamic and Aeroacoustic Characteristics of Small Unmanned Aerial Systems

Abstract: With the rapid increase in the number of multi-rotor small unmanned aerial systems (sUAS) in recent years and a plethora of possible applications, the aerodynamic and aeroacoustic characteristics of these vehicles become very important issues. Due to the limited research on the aerodynamic and aeroacoustic characteristics of sUAS which include an airframe or support arm, this paper presents a comprehensive analysis of the flow and acoustic features with the inclusion of said geometry. The influence of rotor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In addition to the good frequency match, the sound pressure level magnitudes of the first four harmonics match with a difference of 0.5-6 dB (Table 1). This agreement is similar or better compared to more detailed aeroacoustic models of drone and wind turbine rotors, that predict noise due to blade-wake interactions and boundary layer turbulence (55)(56)(57). Further, comparing the measured and predicted spatial acoustic-pressure holograms for the top and front arrays (reconstructed holograms at a plane 8 cm from the bird; Figure 2B), we find that the hologram phase, shape, and magnitude correspond throughout the stroke.…”
Section: Dipole Acoustic Directivity Patterns Align With Gravitationasupporting
confidence: 79%
“…In addition to the good frequency match, the sound pressure level magnitudes of the first four harmonics match with a difference of 0.5-6 dB (Table 1). This agreement is similar or better compared to more detailed aeroacoustic models of drone and wind turbine rotors, that predict noise due to blade-wake interactions and boundary layer turbulence (55)(56)(57). Further, comparing the measured and predicted spatial acoustic-pressure holograms for the top and front arrays (reconstructed holograms at a plane 8 cm from the bird; Figure 2B), we find that the hologram phase, shape, and magnitude correspond throughout the stroke.…”
Section: Dipole Acoustic Directivity Patterns Align With Gravitationasupporting
confidence: 79%
“…Experimental observations have confirmed these effects under the actual flight conditions of a single copter-type propeller [38,39]. The results of CFD investigations have likewise been confirmed by experimental method measurements, indicating that BVI phenomena occur around single copter-type propellers, double coaxial copter-type propellers, multi-rotors, and quad-tilt rotors [38][39][40][41][42]. Kok et al suggested that the turbulence that occurs around the strong down flow under a rotor interferes with a chemical plume tracing (CPT) algorithm, obstructing its function in the detection of chemical agents [22,43].…”
Section: Introductionmentioning
confidence: 53%
“…All compounds were measured; however, due to the limited space in the manuscript, selected results were included whose levels were significant for this specific location. The phenomenon of turbulence is an important issue that is expressed by the analyses of other authors [ 65 , 66 ]. On the day of the measurement, the weather conditions were stable with no wind.…”
Section: Methodsmentioning
confidence: 99%